(untitled) (Sebha University Conference Proceedings, 2025)
This study aimed to identify the impact of using artificial intelligence (AI) technologies on enhancing knowledge management practices from the perspective of faculty members at Najran University. A questionnaire was distributed to 124 faculty members at the university. The study adopted the descriptive analytical method and utilized descriptive statistics and multiple regression analysis. The findings revealed a very high level of AI usage at the university, as well as a high level of knowledge management practices. Furthermore, the study found a statistically significant impact of using AI technologies on overall knowledge management processes at the university. However, no statistically significant impact was found regarding the use of AI technologies on knowledge sharing at Najran University. The study recommended leveraging AI technologies by integrating them into various university activities to improve administrative and academic performance and to enhance knowledge management practices. This includes establishing a dedicated department for knowledge management, allocating training programs for faculty members, promoting a knowledge-sharing culture at Najran University, and adopting a clear strategy for the use of AI technologies in knowledge management processes in alignment with Saudi Vision 2030. The study also emphasized the need to improve the use of AI technologies in knowledge sharing at Najran University by encouraging collaboration and the exchange of expertise.